2021
DOI: 10.3390/ijms222212563
|View full text |Cite
|
Sign up to set email alerts
|

Possible Treatment of Myocardial Infarct Based on Tissue Engineering Using a Cellularized Solid Collagen Scaffold Functionalized with Arg-Glyc-Asp (RGD) Peptide

Abstract: Currently, the clinical impact of cell therapy after a myocardial infarction (MI) is limited by low cell engraftment due to low cell retention, cell death in inflammatory and poor angiogenic infarcted areas, secondary migration. Cells interact with their microenvironment through integrin mechanoreceptors that control their survival/apoptosis/differentiation/migration and proliferation. The association of cells with a three-dimensional material may be a way to improve interactions with their integrins, and thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 175 publications
0
6
0
Order By: Relevance
“…The results indicated that the bare electrodes modied with the cell adhesion molecule RGD or gelatin improved the adhesions of H9C2 cells by forming focal adhesions and the cells showed normal traction force with positive DS and a good spreading status, while the cells had negative DS or DS was close to zero when they adhered to bare electrodes lacking focal adhesions, and these results are consistent with the known behaviors of cell generated forces or traction force, and the modied adhesion molecules conducted and amplied the mechanical force received by the cell. 34,35 Moreover, the DRPC technique was further used to evaluate the effects of two inotropic drugs ISO and VRP on the cytomechanical parameters of H9C2 cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that the bare electrodes modied with the cell adhesion molecule RGD or gelatin improved the adhesions of H9C2 cells by forming focal adhesions and the cells showed normal traction force with positive DS and a good spreading status, while the cells had negative DS or DS was close to zero when they adhered to bare electrodes lacking focal adhesions, and these results are consistent with the known behaviors of cell generated forces or traction force, and the modied adhesion molecules conducted and amplied the mechanical force received by the cell. 34,35 Moreover, the DRPC technique was further used to evaluate the effects of two inotropic drugs ISO and VRP on the cytomechanical parameters of H9C2 cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Use Benefits References Collagen Scaffolds, hydrogels Bioactivity, biodegradability, low toxicity [192][193][194]…”
Section: Methodsmentioning
confidence: 99%
“…Natural biomaterials are inherently biocompatible and biodegradable, and have functional groups that can induce cell attachment, proliferation, and migration, but these polymers have some drawbacks including poor mechanical properties, high variability between donors, and risk of immunogenicity [179,191]. Collagen, the most abundant structural protein in the body, is also one of the most common natural polymers used to engineer the heart [192][193][194]. Other natural polymers used to produce engineered heart include gelatin [195][196][197], alginate [198,199], chitosan [200,201], fibrin [202,203], silk [204][205][206], and decellularized matrices [159,207,208].…”
Section: Biomaterials In Cardiac Tissue Engineeringmentioning
confidence: 99%
“…When an acidic solution of atelocollagen is neutralized and maintained at 37 °C, the collagen fibrils aggregate into a network due to hydrophobic interactions to form a hydrogel. The resulting collagen hydrogel is widely used as a base material for cell adhesion and implantation owing to its high biocompatibility and physiological activity [ 33 , 34 , 35 , 36 ].…”
Section: Hydrogel and Artificial Cell Sheetsmentioning
confidence: 99%